Assessing the climate change impact on Epimedium brevicornu in China with the MaxEnt model - Liu, Quanwei; Zhuo, Zhihang; Wang, Zhiling; Peng, Yaqin; Xu, Danping (Frontiers in Plant Science, 2025)
Epimedium brevicornu is a traditional medicinal plant in China, containing rich and medically valuable extracts. In recent years, the widespread development and application of its extracts have threatened the wild population of E.brevicornu. In order to protect the population of E. brevicornu, this research employed the Maxent model to examine the influence of climate change on the geographical distribution of E. brevicornu and to forecast its potential suitable distribution in China in light of climate change scenarios. The suitable habitat for E. brevicornu is located between 25.13°-39.50°N and 102.46°-118.13°E, mainly distributed across Loess Plateau. Climate change has a significant impact on the geographic distribution of E. brevicornu, with its high suitability zone expected to increase in the future and its centroid shifts towards the southeast direction. The 2050s projections under the Shared Socioeconomic Pathways (SSP) 1-2.6 and SSP2-4.5 scenarios indicated a significant expansion of highly suitable habitats. The analysis of key environmental variables showed that the seasonal variation coefficient of temperature (bio4), the lowest temperature in the coldest month (bio6), annual precipitation (bio12), seasonal variation of precipitation (bio15), human activity (hf), and the average ultraviolet radiation (UV-B3) in the highest month were the key factors affecting E. brevicornu selection of suitable habitats. This study provided important reference for the protection of the wild population of E. brevicornu and the selection of artificial planting areas in the future.